Pitfalls in Echocardiography: Coarctation of the Aorta Presenting as Dilated Cardiomyopathy (DCM) - Wiegand, G.; Schlensak, C.; Hofbeck, M. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
Purpose: The morphologic spectrum of aortic coarctation extends from discrete isthmic obstruction to tubular hypoplasia of the entire aortic arch. Neonates with coarctation frequently present with congestive heart failure and critically reduced perfusion of the descending aorta following ductal closure. During the recent years we observed several infants with coarctation who presented beyond the neonatal period with dilated cardiomyopathy (DCM). We reviewed our patients with coarctation to determine whether this presentation represents an exception or is relevant for the differential diagnosis of children with DCM.Materials and Methods: From 1/2001 to 12/2013 74 babies with isolated coarctation were diagnosed in our institution. 50 patients presented in the neonatal period and 24 patients beyond the first month.Results: 5/74 infants presented after the neonatal period with poorly contractile, dilated left ventricles. Echocardiographic detection of the coarctation was facilitated by application of the ductal view and by Doppler interrogation of the celiac artery revealing a significantly diminished systolic flow velocity. All patients underwent resection of the coarctation and end-to-end anastomosis of the aorta. Postoperative normalization of left ventricular function was observed within a median interval of 2 months.Conclusion: Coarctation of the aorta presenting as DCM accounted for 21 % of our infants with coarctation who presented beyond the neonatal period and 7 % of those in the first year of life. The stenosis was difficult to detect because of its distal location and normal configuration of the aortic arch. Isthmic coarctation should be included in the differential diagnosis of infants with DCM and requires careful examination of the isthmic region in these children.
Keywords: aortic coarctation; dilated cardiomyopathy; infant; congestive heart failure